2013
DOI: 10.1007/s00403-013-1436-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of four novel male androgenetic alopecia susceptibility loci: no association with female pattern hair loss

Abstract: Female pattern hair loss (FPHL) is a common hair loss disorder in women and has a complex mode of inheritance. The etiopathogenesis of FPHL is largely unknown; however, it is hypothesized that FPHL and male pattern baldness [androgenetic alopecia (AGA)] share common genetic susceptibility alleles. Our recent findings indicate that the major AGA locus, an X-chromosome region containing the androgen receptor and the ectodysplasin A2 receptor (EDA2R) genes, may represent a common genetic factor underlying both ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…[25][26][27][28][29][30][31][32][33][34][35] However, convincing genetic loci linked to FPHL remain to be identi-fied, and the potentially important impact of epigenetic factors on FPHL awaits systematic exploration. [25][26][27][28][29][30][31][32][33][34][35] However, convincing genetic loci linked to FPHL remain to be identi-fied, and the potentially important impact of epigenetic factors on FPHL awaits systematic exploration.…”
Section: Female Pattern Hair Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29][30][31][32][33][34][35] However, convincing genetic loci linked to FPHL remain to be identi-fied, and the potentially important impact of epigenetic factors on FPHL awaits systematic exploration. [25][26][27][28][29][30][31][32][33][34][35] However, convincing genetic loci linked to FPHL remain to be identi-fied, and the potentially important impact of epigenetic factors on FPHL awaits systematic exploration.…”
Section: Female Pattern Hair Lossmentioning
confidence: 99%
“…The familial occurrence of FPHL 24 renders linkage to defined susceptibility genes likely, which may well be different from those identified for androgenetic alopecia in males. [25][26][27][28][29][30][31][32][33][34][35] However, convincing genetic loci linked to FPHL remain to be identi-fied, and the potentially important impact of epigenetic factors on FPHL awaits systematic exploration. 21,25,[36][37][38][39][40][41] The epidemiology of FPHL remains unclear and partially contradictory (see below), likely as a reflection of major variations in the populations examined, the inherent ethnic diversity of hair and the techniques by which a diagnosis of FPHL was reached.…”
Section: Female Pattern Hair Lossmentioning
confidence: 99%
“…Early-onset female pattern hair loss (FPHL), which is much more rare than male pattern baldness, seem to share some genetic basis with the male form, such as the X-chromosomal region containing the AR and EDA2R genes [66]. However, various other genes associated with AGA do not seem to be involved in FPHL [67], leaving the aetiology of female hair loss largely unknown as of yet.…”
Section: Hair Loss / Baldnessmentioning
confidence: 98%
“…Although it was previously postulated that AGA and FPHL share a common genetic background [63][64][65], several recent studies examining the known AGA-associated loci in large FPHL cohorts have shown no association of some of these loci with FPHL [66,67].…”
Section: Polygenic Hair Disordersmentioning
confidence: 99%